Thermoplastic elastomer material and preparation method thereof
Through the combination of polyolefin elastomer, styrene block copolymer, wear-resistant polymer and inorganic filler, the thermoplastic elastomer is prepared by using the twin screw extrusion mechanism to solve the problem of insufficient tensile performance and wear resistance in the prior art. , a composition with high tensile strength and low wear amount is achieved.
Patent Information
- Application Number
- CN202310695203.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
AI Technical Summary
There is no thermoplastic elastomer composition that has both good tensile properties and wear resistance.
The thermoplastic elastomer is prepared by melt blending and blending of a double screw extruder using a composition of polyolefin elastomer, a styrene block copolymer, a wear-resistant polymer and an inorganic filler. The preferred conditions include an extrusion temperature of 180 to 220°C and a rotation speed. 200-300 r/min, a composition with excellent wear resistance and mechanical properties was prepared.
The high tensile strength (≥18MPa) and low wear (≤165mm3) of the thermoplastic elastomer are achieved, while improving the wear resistance and mechanical properties of the material.
Smart Images

Figure BDA0004281464060000061 
Figure BDA0004281464060000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of elastomers, and in particular, relates to a thermoplastic elastomer and a preparation method thereof. Background Art
[0002] Thermoplastic elastomer is a polymer material between plastic and rubber. Due to its special mechanical properties, it can partially replace rubber and is widely used in the manufacture of daily products such as rubber tape and rubber shoes, as well as various industrial products such as rubber hoses and rubber parts. In addition, thermoplastic elastomer can also be added to plastics and blended with plastics to enhance the toughness of plastics.
[0003] CN107541004B discloses a load-resistant and fatigue-resistant TPE thermoplastic elastomer and a preparation method thereof. The raw materials of the elastomer are as follows: SEBS, POE, copolymerized PP, liquid polybutylene PB, calcium carbonate, processing lubricant and antioxidant. The above materials are processed by extrusion to prepare a new elastomer, and the obtained elastomer has good load-resistant and fatigue-resistant properties, good resilience, and a tensile strength of ≥15.5MPa.
[0004] CN109735271A discloses a hot melt adhesive based on SEBS and a method thereof. The raw materials of the elastomer are as follows: SEBS, POE, LDPE, paraffin oil, filler, light stabilizer and antioxidant. The above materials are processed by extrusion to prepare a new elastomer, and the obtained elastomer has good high elasticity and high viscosity.
[0005] CN113637283A discloses a high-strength and high-resilience TPE thermoplastic elastomer. The raw materials of the elastomer are as follows: hydrogenated styrene thermoplastic elastomer, filler oil, plasticized reinforcing resin, high elastic composition, filler, antioxidant, lubricant and colorant. The above materials are processed by extrusion to prepare a new type of elastomer, and the obtained elastomer has good resilience, mechanical properties, weather resistance and wear resistance.
[0006] CN107541004B discloses a load-resistant and fatigue-resistant TPE thermoplastic elastomer and a preparation method thereof. The obtained material has good fatigue resistance, but poor tensile strength, and the wear resistance and tensile strength of the product are not tested.
[0007] CN113637283A discloses a high-strength and high-rebound TPE thermoplastic elastomer. The obtained material has good resilience, but the tensile strength of the material is poor, and the wear resistance and tensile strength of the material are not tested.
[0008] There is no prior art providing a thermoplastic elastomer composition having both good tensile properties and abrasion resistance. Summary of the invention
[0009] In view of the technical problems existing in the prior art, the present invention aims to provide a thermoplastic elastomer composition having good tensile properties and wear resistance and a preparation method thereof.
[0010] According to a first aspect of the present invention, there is provided a thermoplastic elastomer composition comprising the following components:
[0011] 40 to 70 parts by weight, preferably 45 to 60 parts by weight of a polyolefin elastomer;
[0012] 30 to 50 parts by weight, preferably 30 to 40 parts by weight of a styrene block copolymer;
[0013] 5 to 30 parts by weight, preferably 6 to 20 parts by weight of a wear-resistant polymer;
[0014] 0 to 30 parts by weight, preferably 0 to 25 parts by weight of an inorganic filler; and
[0015] 0.01 to 1 parts by weight of an antioxidant,
[0016] Wherein, the total weight of the polyolefin elastomer, the styrene block copolymer and the wear-resistant polymer is 100 parts by weight.
[0017] Preferably, the elastomer composition according to the present invention does not contain any softener, for example, the softener may be white oil, paraffin oil and / or naphthenic oil.
[0018] Preferably, the polyolefin elastomer is at least one selected from ethylene-propylene copolymer (EPDM), ethylene-octene copolymer (POE) and ethylene-octene block copolymer (OBC).
[0019] Preferably, the melt flow rate (190°C, 2.16kg) of the polyolefin elastomer is 0.1-2.5g / 10min; more preferably, the melt flow rate (190°C, 2.16kg) is 0.3-2.0g / 10min; more preferably, the melt flow rate (190°C, 2.16kg) of the polyolefin elastomer is 0.3-0.7g / 10min.
[0020] Preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 300,000, and the styrene content is 20wt% to 50wt%; more preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 100,000, and the styrene content is 25wt% to 40wt%.
[0021] Preferably, the styrene block copolymer is at least one selected from styrene / ethylene-butylene / styrene block copolymer (SEBS) and styrene / butadiene / styrene block copolymer (SBS).
[0022] Preferably, the wear-resistant polymer has a Shore hardness of 40D or more; more preferably, the wear-resistant polymer is at least one selected from polyethylene (PE), polypropylene (PP) and acrylonitrile / butadiene / styrene terpolymer (ABS).
[0023] Polyethylene refers to low-density polyethylene and high-density polyethylene, excluding ultra-high molecular weight polyethylene.
[0024] Preferably, the inorganic filler is at least one selected from ceramic powder, alumina, carbon black, carbon nanotubes and carbon fibers.
[0025] Preferably, the antioxidant is at least one selected from hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants, more preferably hindered phenol antioxidants and phosphite antioxidants; further more preferably, the antioxidant is at least one selected from antioxidant 1010, antioxidant 245, antioxidant 168 and antioxidant 626.
[0026] Preferably, the elastomer composition according to the present invention is pressed into a 2 mm thick sheet using a tablet press and cut into standard tensile specimens, and then placed in a test room for 24 hours, and tested using an Instron 5965 testing machine according to the GB / T 528-2009 method to obtain a tensile strength of more than 18 MPa and a 300% elongation strength of more than 5.5 MPa.
[0027] Preferably, the elastomer composition according to the present invention is molded into a sheet with a thickness of 8 mm using a tablet press and cut into a cylinder with a diameter of 16 mm, and then the wear amount measured by a roller wear machine according to the method of GB / T 9867-2008 is 165 mm 3 the following.
[0028] Preferably, the elastomer composition according to the present invention is molded into a 8 mm thick plate using a tablet press, and the Shore hardness obtained by measuring the plate using a hardness tester according to the GB / T6031-2017 method is 75A or more, more preferably 80A or more.
[0029] According to a second aspect of the present invention, there is provided a method for preparing the elastomer composition according to the present invention, comprising the following steps:
[0030] The polyolefin elastomer, styrene block copolymer, wear-resistant polymer, filler and antioxidant are mixed and added into a twin-screw extruder for melt blending and extrusion, and granulation is performed to obtain a thermoplastic elastomer composition.
[0031] Preferably, the conditions for melt blending in a twin-screw extruder are: extrusion temperature of 180 to 220° C.; and extruder speed of 200 to 300 r / min.
[0032] According to a third aspect of the present invention, there is provided a product, which is prepared from the elastomer composition according to the present invention.
[0033] Preferably, the product is a conveyor belt covering rubber, a buffer pad, etc.
[0034] The elastomer composition according to the present invention has excellent wear resistance and mechanical properties, especially the wear loss is 165mm 3 Below, the tensile strength is 18 MPa or more. DETAILED DESCRIPTION
[0035] The testing methods of the relevant performance parameters involved in the following embodiments and comparative examples are as follows:
[0036] raw material
[0037] Ethylene-octene copolymer (POE), Dow Chemical, brand 8150, melt flow rate 0.5 g / 10 min (190 ° C, 2.16 kg); Mooney viscosity (ML1+4@121 ° C) 33, density 0.868 g / cm 3 ;
[0038] Ethylene-propylene copolymer (EPDM), Dow Chemical, brand 4770P, Mooney viscosity (ML1+4@125℃) is 70, density is 0.87g / cm 3 , the melt flow rate is the melt flow rate is 2g / 10min (190℃, 2.16kg);
[0039] Ethylene-octene block copolymer (OBC), Dow Chemical, brand 9077, density 0.869 g / cm 3 , melt flow rate is 0.5g / 10min (190℃, 2.16kg);
[0040] Styrene block copolymer (SEBS), Baling Petrochemical, brand name YH501T, weight average molecular weight of 70,000, styrene content of 30wt%;
[0041] Styrene / butadiene / styrene block copolymer (SBS), Baling Petrochemical, brand name YH-792, molecular weight of 100,000, styrene content of 40wt%;
[0042] High-density polyethylene (HDPE), Yanshan Petrochemical, brand 7600M, melt flow rate 0.3g / 10min (190℃, 2.16kg), Shore hardness 63D;
[0043] Polypropylene (PP), Yulin Chemical, brand K8003, melt flow rate 3g / 10min (190℃, 2.16kg), Shore hardness 65D;
[0044] Acrylonitrile / butadiene / styrene terpolymer (ABS), Takahashi Petrochemical, brand 3513, melt flow rate 10g / 10min (190℃, 10kg), Shore hardness 80D;
[0045] Carbon black (CB), brand N330; purchased from Shanghai Kain Chemical Co., Ltd.;
[0046] Antioxidant A was antioxidant 168, purchased from Qingdao Jiedejia New Material Technology Co., Ltd.;
[0047] Antioxidant B was antioxidant 1010 purchased from Qingdao Jiedejia New Material Technology Co., Ltd.;
[0048] Other raw materials in the examples and comparative examples are all commercially available.
[0049] Test Method
[0050] (1) Tensile modulus test method
[0051] The elastomer composition was pressed into a 2 mm thick sheet using a sheet press and cut into standard tensile specimens. After being placed in a test room for 24 hours, the sheet was tested using an Instron 5965 testing machine according to the GB / T 528-2009 method.
[0052] (2) Determination of wear
[0053] The elastomer composition was molded into a plate with a thickness of 8 mm and cut into a cylinder with a diameter of 16 mm, and then measured using a drum abrasion machine according to the method of GB / T 9867-2008.
[0054] (3) Determination of hardness
[0055] The elastomer composition was molded into a plate with a thickness of 8 mm and measured using a hardness tester according to the GB / T6031-2017 method.
[0056] The present invention will be described in detail below through examples.
[0057] Example 1
[0058] 5.4kg POE, 3.6kg SEBS, 1kg HDPE, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets, wherein the twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0059] Example 2
[0060] 5.1kg POE, 3.4kg SEBS, 1.5kg HDPE, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0061] Example 3
[0062] 4.8kg POE, 3.2kg SEBS, 2kg HDPE, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0063] Example 4
[0064] 4.8kg POE, 3.2kg SEBS, 2kg acrylonitrile / butadiene / styrene terpolymer (ABS) and 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0065] Example 5
[0066] 5.4kg POE, 3.6kg SEBS, 1kg HDPE, 1kg carbon nanotubes, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0067] Example 6
[0068] 5.4kg POE, 3.6kg SEBS, 1kg HDPE, 1.5kg carbon black, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0069] Example 7
[0070] 6.0kg EPDM, 3.0kg SEBS, 1kg PP, 1.5kg carbon black, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain thermoplastic elastomer granules. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0071] Example 8
[0072] 4.0kg OBC, 4.0kg SBS, 2kg HDPE, 1.5kg carbon black, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 1.
[0073] Table 1: Performance test results of the elastomers prepared in Examples 1 to 8
[0074]
[0075] Comparative Example 1
[0076] 6kg POE, 4kg SEBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 2.
[0077] Comparative Example 2
[0078] 5.4kg POE, 3.6kg SEBS, 1kg HDPE, 4kg carbon black, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 2.
[0079] Comparative Example 3
[0080] 5.4kg POE, 3.6kg SEBS, 1kg HDPE, 1kg glass fiber, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 2.
[0081] Comparative Example 4
[0082] 5.4kg POE, 3.6kg SEBS, 1kg ultra-high molecular weight polyethylene, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 2.
[0083] Comparative Example 5
[0084] 3.8kg POE, 5.2kg SEBS, 1kg HDPE, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets, wherein the twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 2.
[0085] Comparative Example 6
[0086] 7.1kg POE, 2.5kg SEBS, 1kg HDPE, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 2.
[0087] Comparative Example 7
[0088] 5.4 kg POE-2 (brand 8200, melt flow rate 5 g / 10 min (190 ° C, 2.16 kg); Mooney viscosity (ML1+4@121 ° C) 24, density 0.870 g / cm 3 ), 3.6kg SEBS, 1kg HDPE and 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded by a twin-screw extruder to obtain thermoplastic elastomer pellets, wherein the twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C. The obtained elastomer composition was tested, and the results are shown in Table 2.
[0089] Table 2: Performance test results of the elastomers prepared in Comparative Examples 1 to 8
[0090]
[0091] From the results in Table 1 and Table 2, it can be seen that the wear resistance, tensile strength and 300% tensile strength of the materials prepared by the system composed of polyolefin elastomer, styrene block copolymer, wear-resistant polymer and antioxidant in Examples 1 to 3 of the present invention are greatly improved, wherein the wear amount is 232 mm compared with that of Comparative Example 1. 3At least 32% improvement. In addition, referring to Examples 4 to 6, adding wear-resistant polymer and inorganic filler to the thermoplastic elastomer system and controlling the dosage ratio of the two, the wear-resistant effect is the best; in addition, in Examples 7 and 8, the ratio of the matrix of the thermoplastic elastomer is changed, and the wear resistance and mechanical properties of the thermoplastic material can be maintained at a good level.
[0092] At the same time, compared with Example 1, no wear-resistant polymer is added in Comparative Example 1, and too much inorganic filler is added in Comparative Example 2 compared with Example 6, which has a great influence on Shore A hardness and tensile strength; compared with Example 5, the type of inorganic filler added in Comparative Example 3 is not suitable, and the wear resistance is not improved; compared with Example 1, the wear-resistant polymer added in Comparative Example 4 is not suitable, and the wear resistance is not improved; the matrix content of the thermoplastic elastomer in Comparative Examples 5 to Comparative Examples 7 exceeds the appropriate range, and the material Shore A, wear resistance, tensile strength and 300% tensile strength are not balanced, and are not suitable for product manufacturing.
[0093] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are within the spirit scope of the present invention.
Claims
1. A thermoplastic elastomer composition comprising the following components: 40 to 70 parts by weight, preferably 45 to 60 parts by weight of a polyolefin elastomer; 30 to 50 parts by weight, preferably 30 to 40 parts by weight of a styrene block copolymer; 5 to 30 parts by weight, preferably 6 to 20 parts by weight of a wear-resistant polymer; 0 to 30 parts by weight, preferably 0 to 25 parts by weight of an inorganic filler; and 0.01 to 1 parts by weight of an antioxidant, in, The total weight of the polyolefin elastomer, the styrene block copolymer and the wear-resistant polymer is 100 parts by weight.
2. The thermoplastic elastomer composition according to claim 1, wherein The elastomeric composition does not contain any softener.
3. The thermoplastic elastomer composition according to claim 1, wherein The polyolefin elastomer is at least one selected from ethylene-propylene copolymer (EPDM), ethylene-octene copolymer (POE) and ethylene-octene block copolymer (OBC); Preferably, the styrene block copolymer is at least one selected from styrene / ethylene-butylene / styrene block copolymer (SEBS) and styrene / butadiene / styrene block copolymer (SBS); Preferably, the wear-resistant polymer has a Shore hardness of 40D or more; more preferably, the wear-resistant polymer is at least one selected from polyethylene (PE), polypropylene (PP) and acrylonitrile / butadiene / styrene terpolymer (ABS); Preferably, the inorganic filler is at least one selected from ceramic powder, alumina, carbon black, carbon nanotubes and carbon fibers.
4. The thermoplastic elastomer composition according to claim 1, wherein The melt flow rate (190°C, 2.16kg) of the polyolefin elastomer is 0.1 to 2.5g / 10min; preferably, the melt flow rate (190°C, 2.16kg) is 0.3 to 2.0g / 10min; Preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 300,000, and the styrene content is 20wt% to 50wt%; more preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 100,000, and the styrene content is 25wt% to 40wt%.
5. The thermoplastic elastomer composition according to claim 1, wherein The antioxidant is at least one selected from hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants, more preferably hindered phenol antioxidants and phosphite antioxidants; further more preferably, the antioxidant is at least one selected from antioxidant 1010, antioxidant 245, antioxidant 168 and antioxidant 626.
6. The thermoplastic elastomer composition according to claim 1, wherein The elastomer composition is pressed into a 2 mm thick sheet by a sheet press and cut into standard tensile specimens, and then placed in a test room for 24 hours, and tested using an Instron 5965 testing machine according to the GB / T 528-2009 method to obtain a tensile strength of more than 18 MPa and a 300% elongation strength of more than 5.5 MPa; Preferably, the elastomer composition is molded into a sheet with a thickness of 8 mm using a tablet press and cut into a cylinder with a diameter of 16 mm, and then the wear amount measured by a roller wear machine according to the GB / T 9867-2008 method is 165 mm 3 the following; Preferably, the elastomer composition is molded into a 8 mm thick plate using a tablet press, and the Shore hardness obtained by measuring the plate using a hardness tester according to the GB / T6031-2017 method is 75A or more, more preferably 80A or more.
7. A method for preparing an elastomer composition according to any one of claims 1 to 6, comprising the following steps: The polyolefin elastomer, styrene block copolymer, wear-resistant polymer, filler and antioxidant are mixed and added into a twin-screw extruder for melt blending and extrusion, and granulation is performed to obtain a thermoplastic elastomer composition.
8. The method for preparing the elastomer composition according to claim 7, wherein: The conditions for melt blending in the twin-screw extruder are: extrusion temperature of 180-220° C.; extruder speed of 200-300 r / min.
9. An article prepared from the elastomeric composition according to any one of claims 1 to 6.
10. The article according to claim 9, wherein The products are conveyor belt covering rubber, buffer pads and the like.
Citation Information
Cited By
TPE composite material for elastic tube and preparation method thereof
CN120554793A
